Bross process: bio-treatment of alkaline slags produced during lead recycling - L. J. Barnes (The Institute of Materials, Minerals and Mining, 1905)
The process for bio-remediation of sulphidic slag (BROSS) operates at 45 degrees C in a neutral (pH 7), aerobic aqueous environment in which sulphide in the slag is converted to sulphate. A two-stage version has been developed that involves quantitative chemical pre-oxidation of total sulphide to thiosulphate, followed by complete biooxidation of thiosulphate to sulphate. Ferric hydroxide, also produced, acts as a flocculant in the bioreactor effluent, concentrating heavy metal precipitates in the thickener as a sludge which can be returned to the smelter. The process has a high sulphate production rate and low acid and nutrient consumptions. Microorganism growth is the rate-limiting stage, requiring a minimum liquid residence time in the bioreactor of about 7 h. Although large quantities of oxygen are needed, sufficient gas mass transfer can be attained in an air-lift reactor. Products are an aqueous stream containing sodium sulphate with only trace levels of toxic heavy metals and a benign, toxic metal-containing sludge